Reconstruction of a Damaged Lower Polar Artery for Kidney Transplantation Using Tubularised Donor Aorta. (16th October 2017) - Vicéns-Morton, A. J.; Callaghan, C.; Olsburgh, J.
Abstract : Introduction . Live donors, extended donor criteria, and the maximum usage of organs with anatomical variants are some of the mechanisms used to increase the number of organs available. Case . We present the case of a kidney transplant, in which the organ had an iatrogenic injury to a lower pole arterial branch during retrieval. The donor was a 35-year-old male (DCD, Maastricht III). The right kidney was accepted; it had three veins in a single cava patch and three renal arteries, the main artery with aorta patch that is 8 cm long. A small lower pole artery was sectioned during retrieval surgery at approximately 1 cm from its origin as well as a third small mid-lower pole artery. The lower pole damaged artery was reconstructed using tubularised aorta patch to a total length of 5 cm. No additional donor vessels had been sent. After construction of the tubulised aorta, E-E anastomosis to the damaged polar artery was done with interrupted 7-0 Prolene sutures. Conclusion . While the waiting list for a kidney continues to rise and we continue to have organ shortness, vascular retrieval injury should not be an absolute contraindication for transplant.